Linkage isomerism dependent on solvent and temperature. Synthesis and structural properties of diamineplatinum(II) complexes of allyl- and diallylmalonate ligands - Lee, YA; Chung, YK; Sohn, YS (AMER CHEMICAL SOC, 1999)
The linkage isomerism between (O,O')- and (O,alkene)-chelates has been investigated for the complexes A(2)PtL(2) (A(2) = 2,2-dimethyl-1,3-propanediamine (DMPDA), trans-(+/-)-1,2-diaminocyclohexane (DACH); L-2 = allylmalonate (AM), diallylmalonate (DAM)). The crystal structures of (DMPDA)Pt(AM). 2H(2)O (tetragonal P4(2)/m, a = 13.614(3) Angstrom, b = 13.614(3) Angstrom, c = 8.451(4) Angstrom, V = 1566.3(9) Angstrom(3), Z = 4, R = 0.0472) and (DMPDA)Pt(DAM). 2H(2)O (monoclinic P2(1)/n, a = 11.021(3) Angstrom, b = 8.996(2) Angstrom, c = 18.765(7) Angstrom, beta = 106.92(3) degrees, V = 1780.0(9) Angstrom(3), Z = 4, R = 0.0531) have been served. Each platinum atom adopts a typical square planar arrangement with two nitrogen atoms in cis positions. However, surprisingly, the AM anionic ligand is coordinated to the platinum atom via (O,O')-chelation mode through its two carboxylate groups with the alkene group uncoordinated in the solid state, breaking the hard/soft rule. The tetradentate DAM ligand is chelated to the platinum atom through one carboxylate and one alkene group resulting in (O,alkene)-chelation mode with another uncoordinated carboxylate and alkene group. Multinuclear (H-1, C-13, and Pt-195) NMR Studies clearly disclose that the linkage isomerism depends on the solvents employed. Both allyl- and diallylmalonate Ligands are chelated exclusively to the platinum(II) atom via (O,O')-mode in dimethylformamide or Me2SO solution whereas only (O,alkene)-chelation mode is observed in an aqueous solution. At room temperature, the complexes both of the AM and DAM ligands exist in methanol as a mixture of (O,O')- and (O,alkene)-modes. Furthermore, interconversion between the two isomers occurs reversibly depending on temperature: the (O,alkene)-chelate is predominant at low temperatures while the (O,O')-chelate is favorable at elevated temperatures.
Keywords: (DIAMINE)PLATINUM(II) COMPLEXES; PLATINUM(II) COMPLEXES; CELL-LINES; COORDINATION; CRYSTAL; ANALOGS; NMR